Activities of indigenous proteases in cow, buffalo and goat milk of Indian subcontinent and their correlation with somatic cell count. (April 2023) - Gautam, Priyae B.; Sharma, Rajan; Atbhaiya, Yashwant; Gandhi, Kamal; Mann, Bimlesh
Abstract: Activities of indigenous proteases such as plasmin, plasminogen-derived and cathepsin D in milk from different milch species (Murrah buffalo, Sahiwal and Gir cow and Alpine × Beetal and Sanen × Beetal goat) varied significantly ( P <0.05) with the stage of lactation. Plasmin and plasminogen-derived activities were highest in goat and cow milk, respectively. Cathepsin D activity was found to be highest in goat milk and lowest in buffalo milk. The plasminogen-derived activity was 5–6 times higher in buffalo and cow milk vis-à-vis plasmin activity while goat milk exhibited a higher plasmin activity than plasminogen-derived activity. Somatic cell count showed a direct influence on protease activity with the highest being in goat milk. The correlation coefficients of the protease(s) activity with the stage of lactation and somatic cell count were positive indicating a direct impact of somatic cells and lactation on it.